Clear Cell Adenocarcinoma of the Female Genital Tract: Long-Term Outcome and Fertility Aspects After Brachytherapy Aimed at a Conservative Treatment. Issue 8 (1st October 2012) - Magné, Nicolas; Chargari, Cyrus; Levy, Antonin; Rodriguez, Carlos; De Vos, Véronique; Gerbaulet, Alain; Duvillard, Pierre; Morice, Philippe; Haie-Meder, Christine
Abstract : Objectives: To assess the outcome and the fertility aspects in the particular population of cervical and/or vaginal clear cell adenocarcinoma (CCA) associated or not to previous in utero diethylstilbestrol exposure. Methods: From January 1970 to December 2003, data from 61 consecutive patients with cervical and/or vaginal histologically proven CCA treated with brachytherapy (BT) aimed at a conservative treatment at the Institut Gustave Roussy as a part of treatment were retrospectively analyzed. Results: The median follow-up was 9.4 years, ranging from 0.3 to 27.4 years. The 5-year specific overall survival rate was 79%. The median time of disease-free survival was 5.8 years. In the subgroup of 42 patients with a cervical CCA, 12 patients tried to be pregnant, 2 patients became pregnant and had miscarriages (P2M2 and P1M1). No pregnancy has been observed in 10 patients exclusively owing to anomalies of the reproductive tract: 6 patients had partial or total diaphragm, 2 patients had an anatomical alteration of the uterus, 1 patient had atrophic endometrium, and 1 patient had primary infertility. In the subgroup of 19 patients with a vaginal CCA, 7 patients tried to be pregnant. All of them had no morphological and/or functional anomalies of the genital tract. Three of 7 patients had delivered healthy babies (P1D1, P2D2, and P3M2D1), and another one had a miscarriage (P1M1). Moreover, all babies were delivered by cesarean section. The pregnancy rate was 10% (6 of 61 patients) with 3 healthy babies. Conclusion: Conservative approach in patients with female genital tract CCA including BT gives good results with good survival rates and an interesting global pregnancy rate.